DINAMIKA USAHA TANI PERKEBUNAN (Studi Pada Petani Perkebunan di Kecamatan Mori Utara Kabupaten Morowali Utara) - Guampe, Feliks Arfid (Universitas Kristen Satya Wacana, 2016)
The dynamics of plantation farming occure in some regions has been widely discussed. One example is the plantation farming at North Moriwali (Indonesian: Morowali Utara). There are two groups of farmers living in North Morowali territory, particularly in the Sub-District of North Mori. The first group chooses to make a living by cultivating cocoa, for the following reasons: 1) avoiding the risk of being lost, 2) Easy access to market, 3) Business capital, and 4) Cocoa is a sustainable plant. The second group is farmers who decide to make replacement on their cocoa plantation to other commodities (commodity change). This article will discuss factors influencing these farmers in making the replacement.Kata Kunci: dinamika perkebunan, perkebunan, petani, kakao, perubahan komoditas.